Immunoglobulin G4-Seronegative Autoimmune Cholangiopathy With Pancreatic and Hepatic Involvement Mimicking as Primary Sclerosing Cholangitis. Issue 4 (20th April 2023) - Achalu, Sudharshan; Berry, Rani; Wei, Mike T.; Banerjee, Subhas; Ghanouni, Pejman; Kambham, Neeraja; Kwo, Paul Y.
ABSTRACT: Immunoglobulin G4-seronegative autoimmune cholangiopathy is a rare cause of biliary strictures. We describe a 27-year-old man presenting with elevated liver enzymes, recurrent cholangitis/bacteremia, biliary strictures, and normal immunoglobulin G4 levels, who was initially diagnosed with primary sclerosing cholangitis, and later listed for transplantation for recurrent bacteremia. Subsequent surveillance imaging demonstrated morphologic changes consistent with biliary strictures and autoimmune pancreatitis. Initiating corticosteroids resulted in liver enzyme normalization and stricture improvement. Diagnosing seronegative autoimmune cholangiopathy remains challenging given similar presentation to primary sclerosing cholangitis. This case highlights importance of a wide differential for biliary strictures, with increased suspicion in those developing pancreatic changes in this setting.